2017
DOI: 10.1080/20786190.2016.1248143
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and metabolic risk in HIV-infected university students: challenges in their monitoring and management

Abstract: This study aims to describe challenges in the management of HIV-infected university students focusing on their nutritional status and metabolic risk. Methods: A cross-sectional, descriptive study design was used to assess the anthropometry, food intake and clinical status of a cohort of known HIV-infected registered students at a South African university. Results: Participants (n = 63) had a mean CD4 cell count of 411 (SD = 219.9) cells/mm 3 , a mean body mass index (BMI) of 28.05 (SD = 7.9) kg/m 2 and only ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…But few studies in Africa have reported on overweight and obesity levels in AYLHIV other than in the context of ART-associated dyslipidaemia [87,111,112]. One study conducted among South African university students living with HIV (the majority aged 20-25 years) found that 21% were overweight and 30% had obesity [113]. Our results are consistent with these ndings and con rm results from a folder review conducted in this same population that reported similar levels of overweight and obesity [35].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…But few studies in Africa have reported on overweight and obesity levels in AYLHIV other than in the context of ART-associated dyslipidaemia [87,111,112]. One study conducted among South African university students living with HIV (the majority aged 20-25 years) found that 21% were overweight and 30% had obesity [113]. Our results are consistent with these ndings and con rm results from a folder review conducted in this same population that reported similar levels of overweight and obesity [35].…”
Section: Discussionsupporting
confidence: 89%
“…Our study adds to the limited evidence base on NCD prevalence and risk factors in AYLHIV in SSA. To our knowledge, only four other studies in SSA have investigated modi able NCD risk factors besides alcohol and substance use in AYLHIV [87,113,122,123]. While our study provides novel ndings for the sub-Saharan African context, we note some limitations.…”
Section: Strengths and Limitationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Another South African study in adults attending three HIV-clinics reported a high prevalence of central obesity, primarily in women -45% (4% in men) [161]. In contrast, in a study conducted in Brazil, only 2.5% of children and adolescents on ART were overweight or obese based on subscapular skinfold thickness and less than 1% had a high WC [165].…”
Section: % Of Participants Were Femalementioning
confidence: 93%
“…One study conducted among South African university students living with HIV (the majority aged 20-25 years) found that 21% were overweight and 30% were obese [161]. Findings from the United States Adolescent Trials Network showed that more than 40% of behaviourally HIV-infected young women (14-24 years) were overweight or obese [162] and approximately 36% of perinatally HIV-infected adolescents were overweight or obese [163].…”
Section: % Of Aylhiv Were Multidimensionally Poormentioning
confidence: 99%